A rare case of bilateral buccal lesions reconstructed with bipaddle submental artery island flap and buccal fat pad flap along with review of literature - Arora, Viresh; Kathuria, Bhushan; Arora, Madhuri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Reconstruction of full-thickness buccal defect involving oral commissure which demanding, it requires restoring competency of commissure besides providing lining for two surfaces simultaneously. Such defects prerequisites a pedicled flap each for mucosal and cutaneous surfaces else a free flap with double-paddle skin is needed. We present a case of a 45-year-old gentleman with bilateral buccal mucosa lesions; left side proliferative squamous cell carcinoma (T4N0M0) infiltrating into the cheek and right-sided large verrucous lesion. Reconstruction of verrucous lesion defect was done with buccal fat pad flap following wide local excision, while the SCC lesion resulting defect was reconstructed with de-epithelized bipaddle submental artery island flap (SAIF). Postoperatively patient had an uneventful recovery. The bipaddled SAIF has emerged as innovative modification of the conventional submental flap for reconstruction of composite oro-facial wounds provides lining for both surfaces, requires a shorter operative time than a free flap and avoids donor site deformity associated with double paddled Pectoralis cutaneous flap. The complexity of bilateral buccal defects and utilization of bipaddled design for reconstruction warrants submission of this case with just two cases reported in the literature.